Cervico-vaginal secretion cytokine profile: A non-invasive approach to study the endometrial receptivity in IVF cycles. - Zanotta, Nunzia; Monasta, Lorenzo; Skerk, Kristina; Luppi, Stefania; Martinelli, Monica; Ricci, Giuseppe; Comar, Manola (Am J Reprod Immunol, 2019)
PROBLEM: Cytokines have a significant role in the process of embryo implantation, trophoblast growth, and differentiation by modulating the immune and endocrine system. The aim of this study was to investigate the profile of a large set of cytokines in the cervico-vaginal washing of women undergoing IVF, to explore the association of these proteins with a good receptive endometrium. METHOD OF STUDY: A cohort of 155 women scheduled for IVF cycle was recruited. All patients were asymptomatic for genitourinary infections and had been screened for chlamydia, mycoplasma, and other bacterial infections. All IVF subjects were treated according to standard clinical and laboratory protocols. A panel of 48 immune factors was analyzed on cervico-vaginal washing, using magnetic bead-based multiplex immunoassays (Bio-Plex, BIO-RAD Laboratories, Milano, Italy). RESULTS: A total of 99 patients reached embryo transfer, of which 31 had a clinical pregnancy. A pattern of four pro-inflammatory immune molecules, IL-12p40, IFN-a, MIF, and MCP3 (P < 0.001), was found significantly up-regulated in the cervico-vaginal fluid of women with clinical pregnancy. A significantly increased expression of IL-9, Gro , and SDF-1 (P < 0.05) was observed in the presence of endometriosis, while high levels of IL-13 and L-15 were associated with ovulatory infertility factor (P < 0.05). CONCLUSION: In this pilot study, we demonstrated that the expression of specific cytokines in the cervico-vaginal washing on the day of oocyte retrieval might have a positive correlation with the potential clinical pregnancy. Therefore, cervico-vaginal secretion cytokine profiling might be a new, non-invasive approach to study the endometrial receptivity in IVF management.

Menstruation-related disseminated intravascular coagulation in an adenomyosis patient: case report and review of the literature. - Cernogoraz, Alice; Schiraldi, Luigi; Bonazza, Deborah; Ricci, Giuseppe (Gynecol Endocrinol, 2019)
Disseminated intravascular coagulation (DIC) is a high mortality coagulopathy that leads to simultaneous thrombotic and bleeding problems. It occurs as a complication in different disease as malignancies, obstetrical catastrophes, bacterial sepsis and traumas. We report on an extremely rare case of acute DIC in a patient with misdiagnosed adenomyosis and massive methrorragia which led to acute kidney failure. The patient was successfully treated with hysterectomy and blood product transfusions; however, a slight reduction of renal function persisted. We were able to confirm the cause-consequence link between adenomyosis and consumptive DIC since we saw the thrombi in the adenomyotic uterus from early hysterectomy specimen. Moreover, this is the first case, for the best of our knowledge, in which systemic consequences persist in an adenomyosis patient who developed a DIC. Early diagnose and treatment of acute DIC is essential for patient's survival and to prevent severe complications: adenomyosis should be kept in mind as a possible cause of DIC when a patient shows up with massive bleeding.

Dysregulated chaperones associated with cell proliferation and negative apoptosis regulation in the uterine leiomyoma. - Ura, Blendi; Scrimin, Federica; Arrigoni, Giorgio; Aloisio, Michelangelo; Monasta, Lorenzo; Ricci, Giuseppe (Oncol Lett, 2018)
Uterine leiomyomas are benign smooth muscle cell tumors that originate from the myometrium. In this study we focus on dysregulated chaperones associated with cell proliferation and apoptosis. Paired tissue samples of 15 leiomyomas and adjacent myometria were obtained and analyzed by two-dimensional gel electrophoresis (2-DE). Mass spectrometry was used for protein identification and western blotting for 2-DE data validation. The values of 6 chaperones were found to be significantly different in the leiomyoma when compared with the myometrium. A total of 4 proteins were upregulated in the leiomyoma and 2 proteins were downregulated. Calreticulin and 78 kDa glucose-regulated protein were further validated by western blotting because the first is considered a marker of cell proliferation, while the second protects against apoptotic cell death. In addition, we also validated the two downregulated proteins heat shock protein β-1 and heat shock 70 kDa protein 1A. Our study shows the existence of a dysregulation of chaperone proteins associated with leiomyoma development. Functional studies are needed to ascertain the role of these chaperones in the leiomyoma. This may be crucial for the further development of specific inhibitors against the activity of these proteins in order to block the growth of the leiomyoma.

Imaging and therapy of ovarian cancer: clinical application of nanoparticles and future perspectives. - Di Lorenzo, Giovanni; Ricci, Giuseppe; Severini, Giovanni Maria; Romano, Federico; Biffi, Stefania (Theranostics, 2018)
Despite significant advances in cancer diagnostics and treatment, ovarian cancers (OC) continue to kill more than 150,000 women every year worldwide. Due to the relatively asymptomatic nature and the advanced stage of the disease at the time of diagnosis, OC is the most lethal gynecologic malignancy. The current treatment for advanced OC relies on the synergistic effect of combining surgical cytoreduction and chemotherapy; however, beside the fact that chemotherapy resistance is a major challenge in OC management, new imaging strategies are needed to target microscopic lesions and improve both cytoreductive surgery and patient outcomes. In this context, nanostructured probes are emerging as a new class of medical tool that can simultaneously provide imaging contrast, target tumor cells, and carry a wide range of medicines resulting in better diagnosis and therapeutic precision. Herein we summarize several exemplary efforts in nanomedicine for addressing unmet clinical needs.

Interstitial Fluid in Gynecologic Tumors and Its Possible Application in the Clinical Practice. - Ura, Blendi; Di Lorenzo, Giovanni; Romano, Federico; Monasta, Lorenzo; Mirenda, Giuseppe; Scrimin, Federica; Ricci, Giuseppe (Int J Mol Sci, 2018)
Gynecologic cancers are an important cause of worldwide mortality. The interstitium consists of solid and fluid phases, situated between the blood vessels and cells. The interstitial fluid (IF), or fluid phase, is an extracellular fluid bathing and surrounding the tissue cells. The TIF (tumor interstitial fluid) is a dynamic fluid rich in lipids, proteins and enzyme-derived substances. The molecules found in the IF may be associated with pathological changes in tissues leading to cancer growth and metastatization. Proteomic techniques have allowed an extensive study of the composition of the TIF as a source of biomarkers for gynecologic cancers. In our review, we analyze the composition of the TIF, its formation process, the sampling methods, the consequences of its accumulation and the proteomic analyses performed, that make TIF valuable for monitoring different types of cancers.
Keywords: Biomarkers, Tumor; Biophysical Phenomena; Extracellular Fluid; Female; Genital Neoplasms, Female; Humans; Practice Patterns, Physicians'; Tumor Microenvironment

Light element distribution in fresh and frozen-thawed human ovarian tissues: a preliminary study. - Pascolo, Lorella; Venturin, Irene; Gianoncelli, Alessandra; Bortul, Roberta; Zito, Gabriella; Giolo, Elena; Salomè, Murielle; Bedolla, Diana E; Altissimo, Matteo; Zweyer, Marina; Ricci, Giuseppe (Reprod Biomed Online, 2018)
RESEARCH QUESTION: Does synchrotron X-ray fluorescence (XRF) provide novel chemical information for the evaluation of human ovarian tissue cryopreservation protocols? DESIGN: Tissues from five patients undergoing laparoscopic surgery for benign gynaecological conditions were fixed for microscopic analysis either immediately or after cryopreservation. After fixation, fresh and slowly frozen samples were selected by light microscopy and transmission electron microscopy, and subsequently analysed with synchrotron XRF microscopy at different incident energies. RESULTS: The distributions of elements detected at 7.3 keV (S, P, K, Cl, Fe, and Os) and 1.5 keV (Na and Mg) were related to the changes revealed by light microscopy and transmission electron microscopy analyses. The light elements showed highly informative findings. The S distribution was found to be an indicator of extracellular component changes in the stromal tissues of the freeze-stored samples, further revealed by the transmission electron microscopy analyses. Low-quality follicles, frequent in the freeze-thawed tissues, showed a high Na level in the ooplasm. On the contrary, good-quality follicles were detected by a homogeneous Cl distribution. The occurrence of vacuolated follicles increased after cryopreservation, and the XRF analyses showed that the vacuolar structures contained mainly Cl and Na. CONCLUSIONS: The study demonstrates that elemental imaging techniques, particularly revealing the distribution of light elements, could be useful in establishing new cryopreservation protocols.
Keywords: Cryopreservation; Female; Humans; Microscopy, Electron, Transmission; Organ Preservation; Ovarian Follicle; Ovary

Meconium-stained amniotic fluid: a risk factor for postpartum hemorrhage. - Bouchè, Carlo; Wiesenfeld, Uri; Ronfani, Luca; Simeone, Roberto; Bogatti, Paolo; Skerk, Kristina; Ricci, Giuseppe (Ther Clin Risk Manag, 2018)
Background/aim: Clinical data with respect to the impact of meconium on the risk of maternal hemorrhage are scarce. Therefore, in this study, we aimed to determine whether meconium-stained amniotic fluid (MSAF) represents a risk factor for postpartum hemorrhage (PPH) after vaginal delivery in a large unselected population. Patients and methods: A retrospective cohort study evaluated 78,542 consecutive women who had a vaginal delivery between 24th and 44th weeks of gestation. The women who had undergone cesarean section were excluded to avoid possible bias. Postpartum blood loss was measured with graduated blood sack. Postpartum blood loss between 1,000 and 2,000 mL and >2,000 mL were classified as moderate and severe PPH, respectively. Results: A total of 74,144 patients were available for analysis. According to the color of amniotic fluid (AF), two groups of patients were identified: MSAF (n=10,997) and clear AF (n=63,147). The rates of severe and massive PPH were found to be significantly higher in the MSAF group than that of clear AF group (OR=1.3, 95% CI: 1.2-1.5, <0.001 and OR=2.5, 95% CI: 1.5-4.2, <0.001). Operative vaginal delivery rate was found to be higher in the MSAF group than that of clear AF group, but the difference was only borderline significant (OR=1.5, 95% CI: 1.0-2.2, =0.05). There were no significant differences between the MSAF and the clear AF groups with respect to episiotomies, second- or third-degree perineal tears, vaginal-perineal thrombus, cervical lacerations, vaginal births after cesarean section, twin deliveries, and placental retention rates. Conclusion: To the best of our knowledge, this is the first clinical study that has investigated the role of MSAF as a risk factor for PPH after vaginal delivery in an unselected population. Our results suggest that MSAF is significantly associated with higher risk of moderate and severe PPH than clear AF.

Pathological Significance and Prognostic Value of Surfactant Protein D in Cancer. - Mangogna, Alessandro; Belmonte, Beatrice; Agostinis, Chiara; Ricci, Giuseppe; Gulino, Alessandro; Ferrara, Ines; Zanconati, Fabrizio; Tripodo, Claudio; Romano, Federico; Kishore, Uday; Bulla, Roberta (Front Immunol, 2018)
Surfactant protein D (SP-D) is a pattern recognition molecule belonging to the Collectin (collagen-containing C-type lectin) family that has pulmonary as well as extra-pulmonary existence. In the lungs, it is a well-established opsonin that can agglutinate a range of microbes, and enhance their clearance phagocytosis and super-oxidative burst. It can interfere with allergen-IgE interaction and suppress basophil and mast cell activation. However, it is now becoming evident that SP-D is likely to be an innate immune surveillance molecule against tumor development. SP-D has been shown to induce apoptosis in sensitized eosinophils derived from allergic patients and a leukemic cell line p53 pathway. Recently, SP-D has been shown to suppress lung cancer progression interference with the epidermal growth factor signaling. In addition, a truncated form of recombinant human SP-D has been reported to induce apoptosis in pancreatic adenocarcinoma Fas-mediated pathway in a p53-independent manner. To further establish a correlation between SP-D presence/levels and normal and cancer tissues, we performed a bioinformatics analysis, using Oncomine dataset and the survival analysis platforms Kaplan-Meier plotter, to assess if SP-D can serve as a potential prognostic marker for human lung cancer, in addition to human gastric, breast, and ovarian cancers. We also analyzed immunohistochemically the presence of SP-D in normal and tumor human tissues. We conclude that (1) in the lung, gastric, and breast cancers, there is a lower expression of SP-D than normal tissues; (2) in ovarian cancer, there is a higher expression of SP-D than normal tissue; and (3) in lung cancer, the presence of SP-D could be associated with a favorable prognosis. On the contrary, at non-pulmonary sites such as gastric, breast, and ovarian cancers, the presence of SP-D could be associated with unfavorable prognosis. Correlation between the levels of SP-D and overall survival requires further investigation. Our analysis involves a large number of dataset; therefore, any trend observed is reliable. Despite apparent complexity within the results, it is evident that cancer tissues that produce less levels of SP-D compared to their normal tissue counterparts are probably less susceptible to SP-D-mediated immune surveillance mechanisms infiltrating immune cells.

Pre-eclampsia affects procalcitonin production in placental tissue. - Agostinis, Chiara; Rami, Damiano; Zacchi, Paola; Bossi, Fleur; Stampalija, Tamara; Mangogna, Alessandro; Amadio, Leonardo; Vidergar, Romana; Vecchi Brumatti, Liza; Ricci, Giuseppe; Celeghini, Claudio; Radillo, Oriano; et al. (Am J Reprod Immunol, 2018)
PROBLEM: Procalcitonin (PCT) is the prohormone of calcitonin which is usually released from neuroendocrine cells of the thyroid gland (parafollicular) and the lungs (K cells). PCT is synthesized by almost all cell types and tissues, including monocytes and parenchymal tissue, upon LPS stimulation. To date, there is no evidence for PCT expression in the placenta both in physiological and pathological conditions. METHOD: Circulating and placental PCT levels were analysed in pre-eclamptic (PE) and control patients. Placental cells and macrophages (PBDM), stimulated with PE sera, were analysed for PCT expression. The effect of anti-TNF-α antibody was analysed. RESULTS: Higher PCT levels were detected in PE sera and in PE placentae compared to healthy women. PE trophoblasts showed increased PCT expression compared to those isolated from healthy placentae. PE sera induced an upregulation of PCT production in macrophages and placental cells. The treatment of PBDM with PE sera in the presence of anti-TNF-α completely abrogated the effect induced by pathologic sera. CONCLUSION: Trophoblast cells are the main producer of PCT in PE placentae. TNF-α, in association with other circulating factors present in PE sera, upregulates PCT production in macrophages and normal placental cells, thus contributing to the observed increased in circulating PCT in PE sera.
Keywords: Adult; Calcitonin; Cohort Studies; Female; Humans; Macrophages; Placenta; Pre-Eclampsia; Pregnancy; Trophoblasts; Tumor Necrosis Factor-alpha; Up-Regulation; Young Adult

Identification of proteins with different abundance associated with cell migration and proliferation in leiomyoma interstitial fluid by proteomics. - Ura, Blendi; Scrimin, Federica; Franchin, Cinzia; Arrigoni, Giorgio; Licastro, Danilo; Monasta, Lorenzo; Ricci, Giuseppe (Oncol Lett, 2017)
Uterine leiomyoma is the most common female reproductive tract benign tumor. Little is known about protein composition and changes in the leiomyoma interstitial fluid (IF). The present study focused on changes in protein abundance in the IF of leiomyoma. Leiomyoma IFs and adjacent myometrial IFs were obtained and analyzed by two-dimensional electrophoresis (2-DE) coupled with mass spectrometry and western blotting for 2-DE data validation. A total of 25 unique proteins were observed to change significantly (P<0.05). Of these proteins with different abundance, 22 had not been previously identified in leiomyoma IF. analysis predicted that three of these proteins were secreted via classical mechanisms, while 22 were secreted via non-classical mechanisms. Ingenuity Pathway Analysis identified 17 proteins associated with cellular migration and proliferation. Among these, phosphoglycerate mutase 1 had not been previously associated with leiomyoma. The abundance of seven proteins was further validated by western blotting. A comparative proteomic approach identified a number of proteins associated with cellular migration and proliferation, with changes in abundance in IF likely to be involved in tumor development. Further studies will be required to investigate the role of these proteins in leiomyoma IF and their possible association with tumor development and growth.

Preoperative Serum Human Epididymis Protein 4 Levels in Early Stage Endometrial Cancer: A Prospective Study. - Fanfani, Francesco; Restaino, Stefano; Cicogna, Stefania; Petrillo, Marco; Montico, Marcella; Perrone, Emanuele; Radillo, Oriano; De Leo, Rossella; Ceccarello, Matteo; Scambia, Giovanni; Ricci, Giuseppe (Int J Gynecol Cancer, 2017)
OBJECTIVE: The aim of the study was to evaluate the prognostic value of human epididymis protein 4 (HE4) and cancer antigen 125 markers with pathological prognostic factor to complete the preoperative clinical panel and help the treatment planning. METHODS: This prospective multicenter study was conducted in 2 gynecologic oncology centers between 2012 and 2014 (Institute for Maternal and Child Health IRCCS Burlo Garofolo in Trieste and Catholic University of the Sacred Heart in Rome, Italy). We enrolled 153 patients diagnosed with clinical early (International Federation of Gynecology and Obstetrics stages I-II) type I endometrial cancer. RESULTS: Human epididymis protein 4 levels seemed to be strictly related to age (P < 0.001) and menopausal status (P < 0.002). Compared with myometrial invasion (MI), the HE4 values were significantly higher in case of invasion of greater than 50% of the thickness: MI of greater than 50%, median of 94.85 pmol/L (38.3-820.8 pmol/L), versus MI of less than 50%, median of 65.65 pmol/L (25.1-360.2 pmol/L), (P < 0.001). The HE4 levels increase significantly with increasing tumor size: diameter of larger than 2 cm, median of 86.9 pmol/L (35.8-820.8 pmol/L), versus diameter of smaller than 2 cm, median of 52.2 pmol/L (33.3-146.8 pmol/L), (P < 0.001). In our population, HE4 did not correlate with the histological grade, endometrial cancer type I versus type II (P = 0.86), the lymphovascular infiltration (P = 0.12), and the cervical invasion (P = 0.6). We established a new variable, considering 3 high-risk tumor features: MI of greater than 50% and/or histological G3 and/or type II. Human epididymis protein 4 levels significantly increase in high-risk tumors (high risk HE4, 93.6 pmol/L vs low-medium risk, 65.5 pmol/L; P < 0.001). CONCLUSIONS: A preoperative HE4 evaluation could help stratify patients with deep invasion and/or metastatic disease and is correlated with other relevant prognostic factors to be considered to tailor an adequate surgical strategy.
Keywords: Adult; Aged; Aged, 80 and over; Biomarkers, Tumor; Endometrial Neoplasms; Female; Humans; Middle Aged; Neoplasm Staging; Preoperative Care; Prognosis; Prospective Studies; Proteins

Subclinical alteration of the cervical-vaginal microbiome in women with idiopathic infertility. - Campisciano, Giuseppina; Florian, Fiorella; D'Eustacchio, Angela; Stanković, David; Ricci, Giuseppe; De Seta, Francesco; Comar, Manola (J Cell Physiol, 2017)
Biomarkers have a wide application in research and clinic, they help to choose the correct treatment for diseases. Recent studies, addressing the vaginal microbiome using next generation sequencing (NGS), reported the involvement of bacterial species in infertility. We compared the vaginal microbiome of idiopathic infertile women with that of healthy, including bacterial vaginosis affected women and non-idiopathic infertile women, to identify bacterial species suitable as biomarkers. Information on microorganisms was obtained from the V3-16S rDNA sequencing of cervical-vaginal fluids of 96 women using the Ion Torrent platform. Data were processed with QIIME and classified against the Vaginal 16S rDNA Reference Database. The analysis revealed a significant beta-diversity variation (p < 0.001) between the four groups included in the study. L. iners, L. crispatus, and L. gasseri distinguished idiopathic infertile women from the other groups. In these women, a microbial profile similar to that observed in bacterial vaginosis women has been detected. Our results suggest that the quantitative assessment and identification of specific microorganisms of the cervical-vaginal microflora could increase the accuracy of available tools for the diagnosis of infertility and improve the adoption of therapeutic protocols.
Keywords: Adult; Biodiversity; Cervix Uteri; Cohort Studies; Demography; Female; Humans; Infertility, Female; Microbiota; Species Specificity; Vagina; Vaginosis, Bacterial

Thrombogenesis in Thrombophilic Pregnancy: Evaluation of Low-Molecular-Weight Heparin Prophylaxis. - Simeone, Roberto; Giacomello, Roberta; Bruno, Germano; Parco, Sergio; Maximova, Natalia; Martinelli, Monica; Zito, Gabriella; Luppi, Stefania; Cervi, Gina; Ricci, Giuseppe (Acta Haematol, 2017)
The aim of this study is to investigate thrombogenesis and the hypercoagulable changes in pregnant women affected by thrombophilia who received low-molecular-weight heparin (LWMH) prophylaxis. We included 21 pregnant women affected by thrombophilia treated with LWMH and 20 nontreated normal pregnant women as the control group. The sample group of thrombophilic pregnant women included different conditions (factor V Leiden mutation, protein C deficiency, protein S deficiency, antiphospholipid antibodies syndrome, and combined defects). Three blood samples were collected during pregnancy (i.e., at 16, 20, and 24 weeks) and tested for activated partial thromboplastin time and prothrombin fragment F1 + 2 (F1 + 2); anti-FXa activity was tested only in treated thrombophilic pregnant women. F1 + 2 levels progressively increased during pregnancy in both study groups. However, the F1 + 2 increase in women exposed to heparin prophylaxis was significantly lower than that in normal pregnant women in all 3 measurements carried out during gestation (p < 0.05); a statistically significant inverse correlation between F1 + 2 levels and anti-Xa activity (R = -0.8575, p < 0.05) was observed in treated women during pregnancy. Our findings suggest that F1 + 2 in addition to anti-Xa measurement could be used to adjust LWMH prophylaxis, at least in high-risk pregnant women.
Keywords: Adult; Anticoagulants; Case-Control Studies; Factor Xa Inhibitors; Female; Heparin, Low-Molecular-Weight; Humans; Nadroparin; Partial Thromboplastin Time; Peptide Fragments; Pilot Projects; Pregnancy; Pregnancy Complications, Hematologic; Prothrombin; Thrombophilia; Thrombosis

Abnormal expression of leiomyoma cytoskeletal proteins involved in cell migration. - Ura, Blendi; Scrimin, Federica; Arrigoni, Giorgio; Athanasakis, Emmanouil; Aloisio, Michelangelo; Monasta, Lorenzo; Ricci, Giuseppe (Oncol Rep, 2016)
Uterine leiomyomas are monoclonal tumors. Several factors are involved in the neoplastic transformation of the myometrium. In our study we focused on dysregulated cytoskeletal proteins in the leiomyoma as compared to the myometrium. Paired tissue samples of ten leiomyomas and adjacent myometria were obtained and analyzed by two‑dimensional gel electrophoresis (2-DE). Mass spectrometry was used for protein identification, and western blotting for 2-DE data validation. The values of ten cytoskeletal proteins were found to be significantly different: eight proteins were upregulated in the leiomyoma and two proteins were downregulated. Three of the upregulated proteins (myosin regulatory light polypeptide 9, four and a half LIM domains protein 1 and LIM and SH3 domain protein 1) are involved in cell migration, while downregulated protein transgelin is involved in replicative senescence. Myosin regulatory light polypeptide 9 (MYL9) was further validated by western blotting because it is considered to be a cell migration marker in several cancers and could play a key role in leiomyoma development. Our data demonstrate significant alterations in the expression of cytoskeletal proteins involved in leiomyoma growth. A better understanding of the involvement of cytoskeletal proteins in leiomyoma pathogenesis may contribute to the identification of new therapeutic targets and the development of new pharmacological approaches.

Incidence and Estimated Prevalence of Endometriosis and Adenomyosis in Northeast Italy: A Data Linkage Study. - Morassutto, Caterina; Monasta, Lorenzo; Ricci, Giuseppe; Barbone, Fabio; Ronfani, Luca (PLoS One, 2016)
Despite being quite frequent and having serious implications in terms of symptomatology and fertility, data on incidence and prevalence of endometriosis and adenomyosis following gold standard definitions are dramatically lacking. The average time from onset of symptoms to diagnosis in industrialized countries still ranges from five to ten years. Using the regional centralized data linkage system, we calculated incidence and prevalence of endometriosis and adenomyosis in the female population of Friuli Venezia Giulia region, Italy, for the years 2011-2013. Cases were defined as new diagnoses from hospital discharge records, following procedures allowing direct visualization for endometriosis and hysterectomy for adenomyosis, with or without histological confirmation. Diagnoses were considered "new" after verifying women had not been diagnosed in the previous ten years. Incidence of endometriosis and adenomyosis in women aged 15-50 years is 0.14%. Prevalence, estimated from incidence, is 2.00%. Adenomyosis, representing 28% of all diagnoses, becomes increasingly prevalent after the age of 50 years. Our results shows how the study of both endometriosis and adenomyosis should not be limited to women of premenopausal age. Further efforts are needed to sensitize women and health professional, and to find new data linkage possibilities to identify undiagnosed cases.

Pitfalls and promises in FTIR spectromicroscopy analyses to monitor iron-mediated DNA damage in sperm. - Pascolo, Lorella; Bedolla, Diana E; Vaccari, Lisa; Venturin, Irene; Cammisuli, Francesca; Gianoncelli, Alessandra; Mitri, Elisa; Giolo, Elena; Luppi, Stefania; Martinelli, Monica; Zweyer, Marina; Ricci, Giuseppe (Reprod Toxicol, 2016)
Many drugs, chemicals, and environmental factors can impair sperm functionality by inducing DNA damage, one of the important causes of reduced fertility potential. The use of vibrational spectromicroscopy represents a promising approach for monitoring DNA integrity in sperm, although some limitations exist, depending from the experimental conditions. Here, we report that when using FTIR spectromicroscopy to reveal oxidative stress mediated by Fenton's reaction on hydrated sperm samples, DNA damage interpretation is partially compromised by unexpected cell surface precipitates. The precipitates give a broad band in the 1150-1000cm(-1) infrared region, which partially covers one of the signatures of DNA (phosphate stretching bands), and are detected as iron and oxygen containing material when using XRF spectroscopy. On the other hand, the analyses further support the potential of FTIR spectromicroscopy to reveal cellular oxidative damage events such as lipid peroxidation, protein misfolding and aggregations, as well as DNA strain breaks.

A Proteomic Approach for the Identification of Up-Regulated Proteins Involved in the Metabolic Process of the Leiomyoma. - Ura, Blendi; Scrimin, Federica; Arrigoni, Giorgio; Franchin, Cinzia; Monasta, Lorenzo; Ricci, Giuseppe (Int J Mol Sci, 2016)
Uterine leiomyoma is the most common benign smooth muscle cell tumor of the uterus. Proteomics is a powerful tool for the analysis of complex mixtures of proteins. In our study, we focused on proteins that were upregulated in the leiomyoma compared to the myometrium. Paired samples of eight leiomyomas and adjacent myometrium were obtained and submitted to two-dimensional gel electrophoresis (2-DE) and mass spectrometry for protein identification and to Western blotting for 2-DE data validation. The comparison between the patterns revealed 24 significantly upregulated (p < 0.05) protein spots, 12 of which were found to be associated with the metabolic processes of the leiomyoma and not with the normal myometrium. The overexpression of seven proteins involved in the metabolic processes of the leiomyoma was further validated by Western blotting and 2D Western blotting. Four of these proteins have never been associated with the leiomyoma before. The 2-DE approach coupled with mass spectrometry, which is among the methods of choice for comparative proteomic studies, identified a number of proteins overexpressed in the leiomyoma and involved in several biological processes, including metabolic processes. A better understanding of the mechanism underlying the overexpression of these proteins may be important for therapeutic purposes.

Effect of seminal leukocytes on in vitro fertilization and intracytoplasmic sperm injection outcomes. - Ricci, Giuseppe; Granzotto, Marilena; Luppi, Stefania; Giolo, Elena; Martinelli, Monica; Zito, Gabriella; Borelli, Massimo (Fertil Steril, 2015)
OBJECTIVE: To investigate the influence of seminal leukocytes on conventional IVF and intracytoplasmic sperm injection (ICSI) outcomes, using a flow cytometry method. DESIGN: Prospective study. SETTING: Tertiary infertility center and research institute. PATIENT(S): One hundred sixty-four couples undergoing conventional IVF or ICSI. INTERVENTION(S): Seminal leukocytes were counted by flow cytometry. MAIN OUTCOME MEASURE(S): Correlation between seminal leukocytes concentration and reproductive outcomes in IVF and ICSI cycles. RESULT(S): The median number of oocytes retrieved, the fertilization and cleavage rate, the median number and grade of embryos transferred, the median number of good-quality embryos transferred, and the median percentage of good-quality embryos from total embryos transferred, in leukocytospermic and non-leukocytospermic patients were not statistically different after either IVF or ICSI. Similarly, there were no significant differences between the two groups for implantation rate and clinical pregnancy rate. Multivariate logistic regression analysis showed that the reproductive outcomes were not influenced by adjustment for female age, infertility diagnosis, number of previous attempts, treatment protocol (GnRH agonist or antagonist), assisted reproduction procedure (IVF or ICSI), and leukocytospermia. By profiling the proper Poisson regression models, no leukocytospermia cut-off value was able to identify the subjects at risk for oocyte fertilization or embryo cleavage failure. CONCLUSION(S): Using a flow cytometry method, we demonstrated that leukocytospermia does not significantly influence IVF or ICSI outcomes. The same results were obtained by using lower or higher cut-off values for leukocytospermia (from 0.2 to 2 × 10(6)/mL).
Keywords: Adult; Female; Fertilization in Vitro; Flow Cytometry; Humans; Leukocytes; Male; Pregnancy; Pregnancy Rate; Prospective Studies; Semen; Sperm Injections, Intracytoplasmic

Hysteroscopic chasing for endometrial cancer in a low-risk population: risks of overinvestigation. - Scrimin, Federica; Wiesenfeld, Uri; Galati, Emanuele F; Monasta, Lorenzo; Ricci, Giuseppe (Arch Gynecol Obstet, 2015)
PURPOSE: To evaluate the appropriateness of the indications for hysteroscopy done, in fertile and postmenopausal women, for the detection of endometrial cancer. METHODS: A retrospective analysis of 2673 consecutive women who underwent office hysteroscopy chasing for endometrial cancer between January 2012 and June 2014. According to their medical history only low-risk women entered the study. RESULTS: A total of 1070 patients entered the study. The main outcome measure was the appropriateness of the indications for hysteroscopy. Appropriateness was assessed on the basis of guidelines of scientific societies and histologic report. According to the algorithm developed for appropriateness, 44 % of procedures resulted in being inappropriate. In reproductive-aged women 57 % of hysteroscopies were inappropriate. In postmenopausal women inappropriate hysteroscopies were 45 %. In reproductive-aged women, the reasons for inappropriateness were: absence of abnormal uterine bleeding (AUB) or AUB without a trial of progestin therapy. In postmenopausal women, the reasons for inappropriateness were: ultrasound report of endometrial thickening or polyp without bleeding. CONCLUSIONS: Hysteroscopy is often recommended for inappropriate indications. More evidence is needed to identify the risks of overinvestigation, overdiagnosis, and related overtreatment and to better identify the threshold beyond which benefits are likely to outweigh harms.

Relevance of random biopsy at the transformation zone when colposcopy is negative. - Wiesenfeld, Uri; Mangino, Francesco Paolo; Toffoletti, Franco Giovanni; Ricci, Giuseppe (Obstet Gynecol, 2015)
Keywords: Cervical Intraepithelial Neoplasia; Colposcopy; Early Detection of Cancer; Female; Humans; Papillomavirus Infections; Precancerous Conditions; Uterine Cervical Neoplasms

Two-dimensional gel electrophoresis analysis of the leiomyoma interstitial fluid reveals altered protein expression with a possible involvement in pathogenesis. - Ura, Blendi; Scrimin, Federica; Zanconati, Fabrizio; Arrigoni, Giorgio; Monasta, Lorenzo; Romano, Andrea; Banco, Rubina; Zweyer, Marina; Milani, Daniela; Ricci, Giuseppe (Oncol Rep, 2015)
Uterine leiomyoma is the most common smooth benign neoplasm. In the present study, we analyzed the global interstitial fluid (IF) profile of leiomyoma vs. normal myometrium to identify protein dysregulation involved in leiomyoma pathogenesis. Two-dimensional gel electrophoresis and mass spectrometry were used to generate and compare the global interstitial fluid profiles of the leiomyoma and of the normal tissue. Two proteins were validated by immunohistochemistry. By comparing the interstitial fluid profile of the leiomyoma with that of the normal myometrium, the levels of seven proteins were found to be significantly different: four structural organization proteins (desmin, prelamin-A/C, transgelin and α-actinin-1), an inflammatory response (α1-antitrypsin), a response to oxidative stress (peroxiredoxin-2), and a folding protein (heat shock 70 kDa protein 1A/1B). Desmin, α1-antitrypsin and peroxiredoxin-2 were upregulated in the leiomyoma, whereas heat shock 70 kDa protein 1A/1B, α-actinin-1, prelamin-A/C and transgelin were downregulated. Desmin and α1-antitrypsin were further validated by immunohistochemistry. By identifying proteins with altered expression levels compared to the myometrium from several pathways of the leiomyoma pathogenesis, we found the leiomyoma interstitial fluid to have a characteristic proteomic profile. A better appreciation of the pathophysiology of the disease can be useful in the development of conservative treatments that serve as viable alternatives to hysterectomy.

Ultrastructural Morphology of Sperm from Human Globozoospermia. - Ricci, Giuseppe; Andolfi, Laura; Zabucchi, Giuliano; Luppi, Stefania; Boscolo, Rita; Martinelli, Monica; Zweyer, Marina; Trevisan, Elisa (Biomed Res Int, 2015)
Globozoospermia is a rare disorder characterized by the presence of sperm with round head, lacking acrosome. Coiling tail around the nucleus has been reported since early human studies, but no specific significance has conferred it. By contrast, studies on animal models suggest that coiling tail around the nucleus could represent a crucial step of defective spermatogenesis, resulting in round-headed sperm. No observations, so far, support the transfer of this hypothesis to human globozoospermia. The purpose of this work was to compare ultrastructural morphology of human and mouse model globozoospermic sperm. Sperm have been investigated by using scanning and transmission electron microscopy. The images that we obtained show significant similarities to those described in GOPC knockout mice, an animal model of globozoospermia. By using this model as reference, we were able to identify the probable steps of the tail coiling process in human globozoospermia. Although we have no evidence that there is the same pathophysiology in man and knocked-out mouse, the similarities between these ultrastructural observations in human and those in the experimental model are very suggestive. This is the first demonstration of the existence of relevant morphological homologies between the tail coiling in animal model and human globozoospermia.

Medical treatments for endometriosis-associated pelvic pain. - Zito, Gabriella; Luppi, Stefania; Giolo, Elena; Martinelli, Monica; Venturin, Irene; Di Lorenzo, Giovanni; Ricci, Giuseppe (Biomed Res Int, 2014)
The main sequelae of endometriosis are represented by infertility and chronic pelvic pain. Chronic pelvic pain causes disability and distress with a very high economic impact. In the last decades, an impressive amount of pharmacological agents have been tested for the treatment of endometriosis-associated pelvic pain. However, only a few of these have been introduced into clinical practice. Following the results of the controlled studies available, to date, the first-line treatment for endometriosis associated pain is still represented by oral contraceptives used continuously. Progestins represent an acceptable alternative. In women with rectovaginal lesions or colorectal endometriosis, norethisterone acetate at low dosage should be preferred. GnRH analogues may be used as second-line treatment, but significant side effects should be taken into account. Nonsteroidal anti-inflammatory drugs are widely used, but there is inconclusive evidence for their efficacy in relieving endometriosis-associated pelvic pain. Other agents such as GnRH antagonist, aromatase inhibitors, immunomodulators, selective progesterone receptor modulators, and histone deacetylase inhibitors seem to be very promising, but there is not enough evidence to support their introduction into routine clinical practice. Some other agents, such as peroxisome proliferator activated receptors-γ ligands, antiangiogenic agents, and melatonin have been proven to be efficacious in animal studies, but they have not yet been tested in clinical studies.
Keywords: Endometriosis; Female; Gonadotropin-Releasing Hormone; Histone Deacetylase Inhibitors; Hormone Antagonists; Humans; Pain Management; Pelvic Pain; Progestins

Risk of Essure microinsert abdominal migration: case report and review of literature. - Ricci, Giuseppe; Restaino, Stefano; Di Lorenzo, Giovanni; Fanfani, Francesco; Scrimin, Federica; Mangino, Francesco P (Ther Clin Risk Manag, 2014)
PURPOSE: To report a case of Essure microinsert abdominal migration and literature review. METHODS: A 41-year-old woman was counseled to undergo Essure sterilization. The procedure was hampered by the presence of endometrial cavity adhesions, obscuring left tubal ostium. By using microscissors the adhesions were progressively lysed. Since the procedure had become very painful, the patient required general anesthesia. Once adhesion lysis was completed, the tubal ostium was well visible. Both devices were then easily introduced into the fallopian tubes. At the end of the procedure, five coils were visible on the right side and five coils on the left side, as recommended. RESULTS: The 3-month hysterosalpingogram follow-up suspected abdominal migration of the left device. Laparoscopy confirmed the device displacement in the left lower abdominal quadrant. Both fallopian tubes and the uterus appeared normal. No signs of perforation were detected. The device was embedded into the omentum, but it was easily removed. Bilateral tubal sterilization was performed by bipolar coagulation. CONCLUSION: There are only 13 cases, including the present, of Essure abdominal migration in the literature. In most cases, abdominal displacement of the microinsert is asymptomatic and does not induce tissue damage. However, in some cases, it may cause a severe adverse event, requiring major surgery. Therefore, removal of the migrated device should be performed as soon as possible. Moreover, during presterilization counseling, the patient should also be correctly informed about the risk of this rare but relevant complication, as well as about the surgical interventions that could be required to solve it.

Soluble TRAIL is present at high concentrations in seminal plasma and promotes spermatozoa survival. - Zauli, Giorgio; Celeghini, Claudio; Monasta, Lorenzo; Martinelli, Monica; Luppi, Stefania; Gonelli, Arianna; Grill, Vittorio; Ricci, Giuseppe; Secchiero, Paola (Reproduction, 2014)
The expression of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL(TNFSF10)) and of its receptors (TRAILR1, TRAILR2, TRAILR3, and TRAILR4) have been documented in testis, but the presence of soluble TRAIL in seminal fluid, as well as the potential physiopathological role of the TRAIL/TRAILR system in spermatozoa, has not been previously investigated. Male donors (n=123) among couples presenting for infertility evaluation were consecutively enrolled in this study. The presence of soluble TRAIL was analyzed in seminal samples by ELISA, while the surface expression of TRAIL receptors was investigated by flow cytometry. High levels of soluble TRAIL were detected in seminal plasma (median, 11 621 pg/ml and mean±s.d., 13 371±8367 pg/ml) and flow cytometric analysis revealed a variable expression of TRAIL receptors in the sperm cellular fraction among different subjects. In addition, the effect of physiologically relevant concentrations of recombinant TRAIL was investigated on survival and motility of spermatozoa. Of interest, the in vitro exposure of capacitated spermatozoa to recombinant TRAIL (10 ng/ml) significantly preserved their overall survival. Therefore, the present study demonstrates for the first time the presence of elevated levels of the anti-inflammatory cytokine TRAIL in seminal fluids. Moreover, the demonstration that recombinant TRAIL promotes spermatozoa survival after capacitation suggests potential therapeutic implications.
Keywords: Adult; Apoptosis; Enzyme-Linked Immunosorbent Assay; Flow Cytometry; Humans; Infertility, Male; Male; Receptors, TNF-Related Apoptosis-Inducing Ligand; Semen; Sperm Capacitation; Sperm Motility; Spermatozoa; TNF-Related Apoptosis-Inducing Ligand

Association between the JC polyomavirus infection and male infertility. - Comar, Manola; Zanotta, Nunzia; Croci, Eleonora; Murru, Immacolata; Marci, Roberto; Pancaldi, Cecilia; Dolcet, Ornella; Luppi, Stefania; Martinelli, Monica; Giolo, Elena; Ricci, Giuseppe; Tognon, Mauro (PLoS One, 2012)
In recent years the incidence of male infertility has increased. Many risk factors have been taken into consideration, including viral infections. Investigations into viral agents and male infertility have mainly been focused on human papillomaviruses, while no reports have been published on polyomaviruses and male infertility. The aim of this study was to verify whether JC virus and BK virus are associated with male infertility. Matched semen and urine samples from 106 infertile males and 100 fertile males, as controls, were analyzed. Specific PCR analyses were carried out to detect and quantify large T (Tag) coding sequences of JCV and BKV. DNA sequencing, carried out in Tag JCV-positive samples, was addressed to viral protein 1 (VP1) coding sequences. The prevalence of JCV Tag sequences in semen and urine samples from infertile males was 34% (72/212), whereas the BKV prevalence was 0.94% (2/212). Specifically, JCV Tag sequences were detected in 24.5% (26/106) of semen and 43.4% (46/106) of urine samples from infertile men. In semen and urine samples from controls the prevalence was 11% and 28%, respectively. A statistically significant difference (p<0.05) in JCV prevalence was disclosed in semen and urine samples of cases vs. controls. A higher JC viral DNA load was detected in samples from infertile males than in controls. In samples from infertile males the JC virus type 2 strain, subtype 2b, was more prevalent than ubiquitous type 1. JCV type 2 strain infection has been found to be associated with male infertility. These data suggest that the JC virus should be taken into consideration as an infectious agent which is responsible for male infertility.
Keywords: Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; BK Virus; Capsid Proteins; DNA, Viral; Humans; Infertility, Male; JC Virus; Male; Molecular Sequence Data; Polyomavirus Infections; Semen; Sequence Analysis, DNA; Tumor Virus Infections

The effects of uterine fundal pressure (Kristeller maneuver) on pelvic floor function after vaginal delivery. - Sartore, Andrea; De Seta, Francesco; Maso, Gianpaolo; Ricci, Giuseppe; Alberico, Salvatore; Borelli, Massimo; Guaschino, Secondo (Arch Gynecol Obstet, 2012)
PURPOSE: To evaluate the role of uterine fundal pressure during the second stage of labor (Kristeller maneuver) on pelvic floor dysfunction (urinary and anal incontinence, genital prolapse, pelvic floor strength). METHODS: 522 primiparous women, enrolled 3 months after vaginal delivery, were divided in two groups: group A (297 women) identifies the women who received Kristeller maneuvers with different indications (e.g. fetal distress, failure to progress, mother exhaustion), group B (225 women) the women without maneuver. Participants were questioned about urogynecological symptoms and examined by Q-tip test, digital test, vaginal perineometry and uroflowmetric stop test score. RESULTS: Mediolateral episiotomies, dyspareunia and perineal pain were significantly higher in Kristeller group, whereas urinary and anal incontinence, genital prolapse and pelvic floor strength were not significantly different between the groups. CONCLUSIONS: Kristeller maneuver does not modify puerperal pelvic floor function but increases the rate of episiotomies.
Keywords: Delivery, Obstetric; Dyspareunia; Dystocia; Episiotomy; Fatigue; Fecal Incontinence; Female; Fetal Distress; Humans; Labor Stage, Second; Pain, Postoperative; Pelvic Floor; Pelvic Organ Prolapse; Perineum; Pregnancy; Pressure; Puerperal Disorders; Urinary Incontinence; Uterus

A real-time polymerase chain reaction-based protocol for low/medium-throughput Y-chromosome microdeletions analysis. - Segat, Ludovica; Padovan, Lara; Doc, Darja; Petix, Vincenzo; Morgutti, Marcello; Crovella, Sergio; Ricci, Giuseppe (Genet Test Mol Biomarkers, 2012)
PURPOSE: We describe a real-time polymerase chain reaction (PCR) protocol based on the fluorescent molecule SYBR Green chemistry, for a low- to medium-throughput analysis of Y-chromosome microdeletions, optimized according to the European guidelines and aimed at making the protocol faster, avoiding post-PCR processing, and simplifying the results interpretation. METHODS: We screened 156 men from the Assisted Reproduction Unit, Department of Obstetrics and Gynecology, Institute for Maternal and Child Health IRCCS Burlo Garofolo (Trieste, Italy), 150 not presenting Y-chromosome microdeletion, and 6 with microdeletions in different azoospermic factor (AZF) regions. For each sample, the Zinc finger Y-chromosomal protein (ZFY), sex-determining region Y (SRY), sY84, sY86, sY127, sY134, sY254, and sY255 loci were analyzed by performing one reaction for each locus. RESULTS: AZF microdeletions were successfully detected in six individuals, confirming the results obtained with commercial kits. CONCLUSION: Our real-time PCR protocol proved to be a rapid, safe, and relatively cheap method that was suitable for a low- to medium-throughput diagnosis of Y-chromosome microdeletion, which allows an analysis of approximately 10 samples (with the addition of positive and negative controls) in a 96-well plate format, or approximately 46 samples in a 384-well plate for all markers simultaneously, in less than 2 h without the need of post-PCR manipulation.
Keywords: Azoospermia; Chromosome Deletion; Chromosomes, Human, Y; Female; Humans; Kruppel-Like Transcription Factors; Male; Real-Time Polymerase Chain Reaction; Sex Chromosome Aberrations; Sex Chromosome Disorders of Sex Development

Management of the adnexal mass. - Ricci, Giuseppe; Zito, Gabriella; Fischer-Tamaro, Leo (Obstet Gynecol, 2011)
Keywords: Female; Humans; Ovarian Neoplasms